Global Economic Slowdown and Economic Growth Stability in Developing Countries: Evidence from Two-Way Fixed Effects Panel Data Analysis, 2010–2024 - Sabarno Dwirianto; Roza Linda; Abdulla Al Mamun; Atika Ananda Sabrina (Journal of Public Power, 2026)
Growth volatility, rather than merely reduced average growth, constitutes an underexplored welfare-critical consequence of global economic slowdowns in developing countries. Using a two-way fixed effects panel regression on 10 developing countries over 2010–2024, validated through Driscoll-Kraay correction and System-GMM endogeneity control, this study estimates how global GDP growth contractions amplify domestic output volatility operationalized as the rolling five-year standard deviation of annual real GDP growth rates and examines the conditioning roles of trade openness, foreign direct investment (FDI), and inflation as macroeconomic channels. Four robust findings emerge: (1) global slowdowns significantly increase growth volatility (β = −0.482, p < 0.001); (2) trade openness stabilizes growth under normal conditions (β = 0.214, p < 0.05); (3) FDI exhibits the strongest stabilizing effect (β = 0.367, p < 0.001), robust to endogeneity correction; and (4) inflation amplifies volatility by eroding countercyclical monetary policy space (β = −0.291, p < 0.001). These findings reframe growth volatility as the primary indicator of macroeconomic resilience, with policy implications for export diversification, countercyclical FDI frameworks, and central bank institutional independence as structural components of shock absorption capacity in developing economies.